The effect of financial literacy on Gen-Z crypto investment decision through herding behavior as mediator - Arriqoh, Dhiyyah; Zoraya, Intan (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
The progression of investment in Indonesia has witnessed rapid growth, particularly in the realm of crypto assets. By April 2023, the number of crypto investors in Indonesia had surged to 17 million, with the Gen Z cohort dominating this category of asset investors. The primary objective of this research is to examine whether herding behavior can mediate the relationship between financial literacy and crypto investment decisions among Gen Z individuals. This investigation was conducted among crypto investors residing in the city of Bengkulu. A total of 156 individuals were selected as the sample. The collected data was subsequently processed using the Smart PLS 3 application. The research findings indicate that financial literacy has a significantly positive influence on herding, and financial literacy also has a significantly positive impact on the crypto investment decisions of Gen Z. Moreover, herding serves as a mediating factor in the relationship between financial literacy and Gen Z's crypto investment decisions.